Automatic price appraisals: why they matter and how to measure them - Altenburg, Daria; Spruyt, Adriaan (Frontiers in Psychology, 2024)
Accurately estimating consumers' willingness-to-pay (WTP) is crucial to product design, pricing decisions, and the design of competitive marketing strategies. However, traditional selfreport measures of WTP are susceptible to many reporting biases, including tactical responding or an inability to make accurate estimates. Importantly, appraisals also occur automatically (i.e., in the absence of substantial time, intention, awareness, and/or substantial cognitive resources) and implicit measures used to capture automatic appraisals are less susceptible to the sort of reporting biases that self-report measures can be affected by. Yet, existing implicit measures cannot accommodate the testing of a range of prices and the only attempt to develop a measure of automatic price appraisals to date (the Task Rule Congruency paradigm, TRC) was severely limited in its utility by the large amount of time and measurement trials it requires. Accordingly, here we introduce the Implicit Attribute Classification Task (IMPACT), test its effectiveness for the measurement of automatic price appraisals (Study 1), and directly compare its effectiveness and utility with that of the TRC (Study 2). We find that the IMPACT is an efficient measure of automatic price appraisals, that it produces considerably larger effects compared to the TRC, and that it does so while substantially shortening the procedure. We also discuss how the IMPACT scores can be used to derive an implicit measure of willingness to pay. Our findings make a substantial contribution to both research and practice by providing an effective tool that facilitates, for the first time, an efficient exploration of implicit WTP.